Clinical identification and microbiota analysis of Chlamydia psittaci- and Chlamydia abortus- pneumonia by metagenomic next-generation sequencing - Xie, Gongxun; Hu, Qing; Cao, Xuefang; Wu, Wenjie; Dai, Penghui; Guo, Wei; Wang, Ouxi; Wei, Liang; Ren, Ruotong; Li, Yanchun (Frontiers in Cellular and Infection Microbiology, 2023)
Recently, the incidence of chlamydial pneumonia caused by rare pathogens such as C. psittaci or C. abortus has shown a significant upward trend. The non-specific clinical manifestations and the limitations of traditional pathogen identification methods determine that chlamydial pneumonia is likely to be poorly diagnosed or even misdiagnosed, and may further result in delayed treatment or unnecessary antibiotic use. mNGS's non-preference and high sensitivity give us the opportunity to obtain more sensitive detection results than traditional methods for rare pathogens such as C. psittaci or C. abortus. In the present study, we first investigated the pathogenic profile characteristics of pneumonia patients with different chlamydial infection patterns using mNGS. More co-infecting pathogens were found to be detectable in clinical samples from patients infected with C. psittaci compared to C. abortus, suggesting that patients infected with C. psittaci may have a higher risk of mixed infection, which in turn leads to more severe clinical symptoms and a longer disease course cycle. Further, we also used mNGS data to analyze for the first time the characteristic differences in the lower respiratory tract microbiota of patients with and without chlamydial pneumonia, the impact of the pattern of Chlamydia infection on the lower respiratory tract microbiota, and the clinical relevance of these characteristics. Significantly different profiles of lower respiratory tract microbiota and microecological diversity were found among different clinical subgroups, and in particular, mixed infections with C. psittaci and C. abortus resulted in lower lung microbiota diversity, suggesting that chlamydial infections shape the unique lung microbiota pathology, while mixed infections with different Chlamydia may have important effects on the composition and diversity of the lung microbiota. Taken together, the present study provides possible evidences supporting the close correlation between chlamydial infection, altered microbial diversity in patients' lungs and clinical parameters associated with infection or inflammation in patients, which also provides a new research direction to better understand the pathogenic mechanisms of pulmonary infections caused by Chlamydia.